2020
DOI: 10.4103/njms.njms_6_19
|View full text |Cite|
|
Sign up to set email alerts
|

Perception and outcome of oral cancer awareness among clinical undergraduate dental students of Tertiary health care centre at Kanpur city: A cross-sectional study

Abstract: Background: The International Agency for Research on Cancer has predicted that India's incidence of cancer will increase from 1 million in 2012 to more than 1.7 million in 2035. Lack of knowledge about oral cancer among general dental practitioners leads to delay in the diagnosis and treatment of such lesions. The aim of the present study was to investigate the awareness and knowledge of prevention and early diagnosis of oral cancer among dental undergraduate students. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
6
0
4
Order By: Relevance
“…In the study of Srivastava et al, 100% of students reported feeling well informed about the clinical appearance of oral cancer. However, 69.7% of the same students reported insufficient knowledge about the prevention and detection of oral cancer [ 20 ]. This discrepancy between existing theoretical knowledge and practical applications might be reduced by using a structured questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Srivastava et al, 100% of students reported feeling well informed about the clinical appearance of oral cancer. However, 69.7% of the same students reported insufficient knowledge about the prevention and detection of oral cancer [ 20 ]. This discrepancy between existing theoretical knowledge and practical applications might be reduced by using a structured questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate and standardized concept regarding the assessment of the oral mucosa is missing in undergraduate dental curricula. This leads to uncertainty among students [ 18 , 19 , 20 ]. In particular, potentially malignant disorders are often misjudged [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of questionnaires have been used and interviews have been conducted with medical and dental students from different courses [1][2][3]7,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] dental hygiene and nursing students, 47 postgraduate students, 34 professors from different medical and dental specialities, 9,33,48 graduate dentists 1,48 and even health professionals from other disparate fields. 26 In the present study, 4th and 5th year dental students were surveyed.…”
Section: Oscc Knowledgementioning
confidence: 99%
“…In addition to the rigorous training, dental undergraduates are expected to learn specific psychomotor skills required in dentistry. Gender, an intense academic curriculum, the pressure to complete a certain number of clinical cases in a limited amount of time, examinations and grades, fear of academic failure, and uncertain job employment have all been linked to stress among dental students [15][16][17] . Babar et al (2015) 18 confirmed these factors when they investigated perceived stressors among Malaysian dental students.…”
Section: Introductionmentioning
confidence: 99%